Mimicking horseradish peroxidase and oxidase using ruthenium nanomaterials. Issue 82 (10th November 2017) - Cao, Gao-Juan; Jiang, Xiumei; Zhang, Hui; Croley, Timothy R.; Yin, Jun-Jie
Abstract : Ru NPs could catalyze the oxidation of 3, 3, 5, 5-tetramethylbenzidine, o -phenylenediamine and dopamine hydrochloride in the presence of H2 O2, and also catalyze the oxidization of 3, 3, 5, 5-tetramethylbenzidine and sodiuml -ascorbate by dissolved oxygen. Abstract : Although important progress has been achieved for the study of noble metal-based enzyme-like catalysts, there are rare reports on the enzyme mimicking applications of ruthenium nanoparticles (Ru NPs). In this work, we investigated the horseradish peroxidase (HRP) and oxidase mimetic activity of Ru NPs. Mimicking HRP, Ru NPs could catalyze the oxidation of substrates 3, 3, 5, 5-tetramethylbenzidine (TMB), o -phenylenediamine (OPD) and dopamine hydrochloride (DA) in the presence of exogenously added H2 O2 to generate the products with blue, yellow and orange colors, respectively. We also report the first evidence that Ru NPs possess intrinsic oxidase-like activity, which could catalyze the oxidization of TMB and sodiuml -ascorbate (NaA) by dissolved oxygen. The HRP-like and oxidase-like activities of Ru NPs were found to be related to the concentrations of Ru NPs. The catalytic mechanism was analyzed by electron spin resonance spectroscopy (ESR), which suggested that the enzyme mimicking activities of the Ru NPs might originate from their characteristic of accelerating electron transfer between substrates and H2 O2 or O2 . Our findings offer a better understanding of enzyme-mimicking Ru NPs and should provide important insights for future applications.